Protected Areas and Soil Loss: Evidence from the Lugenda River Basin, Mozambique - Alaniz-Baeza, A (Elsevier B.V., 2025)
Soil erosion is a natural geomorphological process intensified by human activities, especially shifting cultivation. Despite the relevance of the topic, there are still few quantitative assessments of soil loss in Mozambique, particularly in river basins that include protected areas. This study provides evidence on how protected areas mitigate soil loss through a multitemporal analysis in the Lugenda River Basin in northern Mozambique, highlighting the role of the Niassa Special Reserve (NSR) in dealing with land use pressure and rainfall variations. The Revised Universal Soil Loss Eq. (RUSLE) was used, integrated with Geographic Information System (GIS) tools, with data on precipitation, topography, soil texture, and vegetation cover to estimate soil loss over five-year intervals between 2000 and 2019. Different types of land use were assessed in the basin, both within and outside the NSR, allowing for comparison of erosion patterns based on land cover and land governance. The results indicated an average loss of approximately 6 tons ha⁻¹ year⁻¹. Between 2000 and 2005, erosion decreased almost half due to reduced rainfall erosivity and improved vegetation cover; however, from 2005 to 2019, there was an uninterrupted increase, driven by increased erosivity and vegetation decline. Agricultural areas and grassland outside the NSR showed the greatest losses, reaching 41 and 20 tons ha⁻¹ year⁻¹ each, while forests and wetlands within the reserve had greater protective capacity. These findings demonstrate that the NSR plays a crucial role in soil conservation by keeping erosion low, but they also reveal increasing risks associated with agricultural intensification and climate variability. The incorporation of conservation practices and the maintenance of protected areas emerge as priority strategies to reduce soil degradation, ensure environmental resilience, and support local and national sustainable management policies. © 2025